Insights into the metabolic profiling of Polygonati Rhizoma fermented by Lactiplantibacillus plantarum under aerobic and anaerobic conditions using a UHPLC-QE-MS/MS system - ZiLing Wang; ZiLing Wang; Jia Lao; XingYi Kang; ZhenNi Xie; ZhenNi Xie; Wei He; XiaoLiu Liu; XiaoLiu Liu; Can Zhong; ShuiHan Zhang; Jian Jin (Frontiers in Nutrition, 2023)
IntroductionPolygonati Rhizoma is a multi-purpose food with medicinal uses. Fermentation of Polygonati Rhizoma by lactic acid bacteria could provide new insights into the development of Polygonati Rhizoma products.MethodsIn this study, Lactiplantibacillus plantarum was fermented with Polygonati Rhizoma extracts in a bioreactor under aerobic and anaerobic conditions with pH and DO real-time detection. Metabolic profiling was determined by UHPLC-QE-MS/MS system. Principal component analysis and orthogonal partial least-squares discriminant analysis were used to perform multivariate analysis.ResultsA total of 98 differential metabolites were identified in broth after fermentation, and 36 were identified between fermentation under aerobic and anaerobic conditions. The main metabolic pathways in the fermentation process are ABC transport and amino acid biosynthesis. Most of the compounds such as L-arginine, L-aspartic acid, leucine, L-lysine, citrate, inosine, carnitine, betaine, and thiamine were significantly increased during fermentation, playing a role in enhancing food flavor. Compared with anaerobic fermentation, aerobic conditions led to a significant rise in the levels of some compounds such as valine, isoleucine, and glutamate; this increase was mainly related to branched-chain amino acid transaminase, isocitrate dehydrogenase, and glutamate dehydrogenase.DiscussionAerobic fermentation is more beneficial for the fermentation of Polygonati Rhizoma by L. plantarum to produce flavor and functional substances. This study is the first report on the fermentation of Polygonati Rhizoma by L. plantarum and provides insights that would be applicable in the development of Polygonati Rhizoma fermented products.